Determination of Yield and Quality Properties of Different Flax (Linum usitatissimum L.) Genotypes in Eskisehir Ecological Conditions - KATAR, Nimet; YAŞAR, Mustafa; KÖSE, Arzu; KATAR, Duran (MAS Journal of Applied Sciences, 2023)
This research was conducted to determine the performance of different flax (Linum usitatissimum L.) genotypes (Sari-85, Clli 1351, Clli 1370, Clli 1400, Clli 1412, Clli 1423, Larnaka, Milas, NewTurk and Dillman) in terms of the plant height, first branch height, number of branches per plant, number of capsules per plant, number of seeds per capsule, 1000 seed weight, the seed yield, oil content, oil yield and fatty acid composition. The mean values of the plant height, first branch height, number of branches per plant, number of capsules per plant, number of seeds per capsule, 1000 seed weight, the seed yield, oil content and oil yield were determined as 62.80 cm, 35.93 cm, 3.51 number, 28.40 number, 11.73 number, 5.80 g, 1.75 t ha-1, 34.84% and 0.61 t ha-1, respectively. α-Linolenic (51.90-58.93%), oleic (16.08-21.78%), linoleic (12.90-16.00%), palmitic (5.70-6.31) and steraric (4.41-5.67%) fatty acids were determined in flax genotypes. The linen genotypes used in the study have been found to have linolenic acid content which is too high to be used as edible oil. Therefore, new genotypes with less than 3% α-linolenic acid content for edible oil production should be developed by breeding programs/biotechnology.